Pengaruh Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian Smartphone Iphone Pada Mahasiswa di Universitas Mataram - Baiq Lani Septia Lestari; Emilia Septiani (Postgraduate, University of Mataram, 2021)
This study aims to analyze the effect of brand image and product quality on iPhone smartphone purchasing decisions among students at the University of Mataram. This type of research used in this research is associative with a quantitative approach. The sampling technique was determined by purposive sampling method with a total of 100 respondents. The data collection tools used a questionnaire and google form which had been tested for validity and reliability. The data analysis technique used is multiple linear regression. The results of this study indicate that: (1) There is a positive and significant influence of brand image variables on purchasing decisions, (2) There is a positive and significant influence on product quality variables on iPhone smartphone purchasing decisions among students at the University of Mataram